Implementación de procesos en la administración efectiva de los materiales de construcción, durante la ejecución de obras en la UTPL. - Mayta Zapata, Swmak Sara (2014)
The main aim of the current research is to formulate an administrative process, which helps to the efficent control and material flow in the execution of civil and architectural works. Moreover monitoring the rules of quality fulfilment determined by Código Ecuatoriano de la Construcción, Norma Técnica Ecuatoriana de la Construcción (NTE INEN), Reglamento Técnico Ecuatoriano (RTE INEN) loooking for the quality of finished work. Documents that allow to base and carry out the work residence, which allows to diagnose the different shortcomings have, the different administrative processes in the execution of Works at the Particular Technical University of Loja. The method of study of this Project is practical, therefore we have set out a “Manual of administration, control and material flow in work” looking for providing to the builder the fast access to the different regulations (Código Ecuatoriano de la Construcción) and its correct application. Moreover we seek to cultivate the use of new technological tools in the field of construction.